FDA Drug Approval Summary: Bevacizumab plus Interferon for Advanced Renal Cell Carcinoma - Summers, Jeff (AlphaMed Press, 2010)
On July 31, 2009, the U.S. Food and Drug Administration granted approval for the use of bevacizumab (Avastin®; Genentech, Inc., South San Francisco, CA) in combination with interferon (IFN)-α2a for the treatment of patients with metastatic renal cell carcinoma. The approval was primarily based on results from a randomized, double-blind, placebo-controlled clinical trial. The primary efficacy endpoint, progression-free survival (PFS), was assessed by investigators and by an independent review committee (IRC) blinded to treatment assignment. In total, 649 patients (bevacizumab plus IFN, 327; placebo plus IFN, 322) were enrolled. The median PFS times, by investigator determination, were 10.2 months for the bevacizumab plus IFN arm and 5.4 months for the placebo plus IFN arm (hazard ratio [HR], 0.60; 95% confidence interval [CI], 0.49–0.72; p < .0001). The IRC analysis of 569 patients with available radiographs yielded similar results (median PFS time, 10.4 months versus 5.5 months; HR, 0.57; 95% CI, 0.45–0.72; p < .0001). There was no survival advantage (HR, 0.86; 95% CI, 0.72–1.04; p = .13). Support for the above results was provided by summarized results of a North American cooperative group study of bevacizumab plus IFN-α2b versus IFN-α2b alone. The median PFS times were 8.4 months versus 4.9 months in favor of the bevacizumab combination. There was no survival advantage. In the reviewed trial, serious adverse events and National Cancer Institute Common Terminology Criteria for Adverse Events grade ≥3 adverse events were reported more frequently in bevacizumab-treated patients (31% versus 19% and 63% versus 47%, respectively). The most common bevacizumab-related toxicities were bleeding/hemorrhage, hypertension, proteinuria, and venous or arterial thromboembolic events.